Timed "Up & Go" test in children and adolescents - Renata D'Agostini Nicolini-Panisson; Márcio Vinícius F. Donadio (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE To evaluate, by a literature review, the Timed "Up & Go" (TUG) test use and its main methodological aspects in children and adolescents. DATA SOURCES The searches were performed in the following databases: PubMed, CINAHL, Web of Science, SciELO and Cochrane Library, from April to July 2012. Studies published from 1990 to 2012 using the terms in Portuguese and English "Timed "Up & Go", "test", "balance", "child", and "adolescent" were selected. The results were divided into categories: general characteristics of the studies, population, test implementation METHODS, interpretation of results and associations with other measurements. DATA SYNTHESIS 27 studies were analyzed in this review and most of them used the TUG test along with other outcome measures to assess functional mobility or balance. Three studies evaluated the TUG test in significant samples of children and adolescents with typical development, and the most studied specific diagnoses were cerebral palsy and traumatic brain injury. The absence of methodological standardization was noted, but one study proposed adaptations to the pediatric population. In children and adolescents with specific clinical diagnoses, the coefficient of within-session reliability was found to be high in most studies, as well as the intra and inter-examiner reliability, which characterizes the good reproducibility of the test. CONCLUSIONS The TUG test was shown to be a good tool to assess functional mobility in the pediatric population, presenting a good reproducibility and correlation with other assessment tools.